Experimental and theoretical study of catalytic and radiative characteristics of anti-oxidation and anti-erosion coatings for high-speed aircraft - O. V. Tushavina (Учёные записки Казанского университета: Серия Физико-математические науки, 2024)
The catalytic activity coefficient and emissivity of the surface of thin-walled oxidation- and erosion-resistant coatings for high-speed aircraft were determined experimentally and theoretically. The coating was applied as an aerosol mixture to a carbon-carbon composite substrate, and the resulting sample was subjected to fully dissociated air to measure heat fluxes to the sample surface and its enthalpy. Using established relationships between total convective-diffusive heat fluxes, stagnation enthalpy, and the heterogeneous recombination coefficient of oxygen and nitrogen atoms into molecules, the catalytic activity coefficient and surface emissivity were calculated based on the Stefan–Boltzmann law utilizing the measured enthalpy (and temperature) of the wall. The experiments were performed on five coating types containing silicon, titanium, molybdenum, and boron. The findings were summarized in a table showing how the recombination coefficient and emissivity depend on heat fluxes and wall temperature.